Dörfer und Deputierte Die Wahlen zu den konstituierenden Parlamenten von 1848 in Niederösterreich und im Pariser Umland (Seine-et-Oise) - Stockinger, Thomas (2012)
The manuscript deals with the elections to the Austrian Constituent Diet in June 1848, compared with those to the French National Assembly in April of the same year, with a focus on the dissemination of new concepts and practices of politics - particularly electoral and representative politics - in rural areas. The approach is based on concepts from the debate on the "politicisation" of rural populations which has been conducted in France during the past decades. To facilitate a detailed analysis closely based on primary sources, the study is limited to the province of Lower Austria (excluding Vienna) and the former department of Seine-et-Oise, surrounding Paris. The manuscript is based on a dissertation accepted in 2010, which has been revised in both content and form. Additional archival research in France in January and February 2011 has allowed an augmentation of the primary source basis. After a summary of theoretical and methodical positions regarding the use of international comparison, a brief presentation of the debates on "politicisation" is intended to familiarize the reader both with the concept and with recent criticisms of it (Chapter 2). The resulting approach is based on the idea not of "politicization" versus a prior "apolitical" condition of rural populations, but rather of a complex of interconnected but not identical shifts in rural concepts and practices of politics. In a first section, demographic, economic and social conditions of the two regions are presented and compared (Chapter 3), as are intellectual preconditions regarding mobility, literacy, religious behavior, and prior experiences with political participation (Chapter 4). The revolutions of 1848 are described with particular attention devoted to the forms they took in rural areas (Chapter 5). The legal and normative framework of the elections is compared in detail, as are administrative prepa¬rations and the processes of electoral information (Chapter 6). These are viewed as efforts by which models of electoral politics, proposed by new and old political elites in both countries, were put before the populations using the power and communicative resources at the disposal of the elites. The elections themselves are first closely described under their procedural aspect; then an analysis of voting behaviour is attempted (Chapter 7). These multiple perspectives demonstrate that divergent notions of the meaning and function of elections competed, but also intermixed. This concerns not only rivalry between the elite-proposed models described in Chapter 6, but also their meeting with concepts held by members of the wider population. In Lower Austria, large numbers of rural voters either rejected or, more frequently, reinterpreted and subverted the proposed electoral model on the basis older practices of political articu¬lation predicated on a corporate subdivision of society. In Seine-et-Oise, behaviors pointing to divergent notions of election are comparatively marginal next to a widespread acceptance of the proposed model. Although the two cases studied differ considerably from one another, and both have only quite limited resemblance to late 20th-century ideals of democratic elections, both can be situated within a complex history of the gradual displacement of older concepts of elections specifically and of politics in general by elements of those familiar in the present.